2010
DOI: 10.1002/anie.201002036
|View full text |Cite
|
Sign up to set email alerts
|

The Driving Mechanism Behind Attrition‐Enhanced Deracemization

Abstract: Change of heart: A solution‐phase enantiomeric excess that has the handedness of the minor population of the solid phase is observed during grinding of a slurry of racemic conglomerate crystals. This excess is the driving force for a net flux of molecules from crystals of the minor handedness to crystals of the major handedness, thus explaining the complete deracemization of the solid phase (see picture: blue: S form, red: R form).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(167 citation statements)
references
References 35 publications
(32 reference statements)
4
161
0
1
Order By: Relevance
“…This result clearly shows that the majority in the solid phase is minority in the solution phase, in qualitative agreement to the experimental result. Therefore, this experiment [24] does not yet give a definitive answer about the correct scenario. Further exploration is necessary.…”
Section: Summary and Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This result clearly shows that the majority in the solid phase is minority in the solution phase, in qualitative agreement to the experimental result. Therefore, this experiment [24] does not yet give a definitive answer about the correct scenario. Further exploration is necessary.…”
Section: Summary and Discussionmentioning
confidence: 79%
“…Thus summarized, we conclude that there are three different scenarios so far, and further experimental works are needed to decide which is the actual mechanism. Recently an experiment has been carried out on the measurement of enantiomeric excess in solution phase ee l as a function of that in solid phase ee s under the absence of racemization process in the solution [24]. It is found that ee l and ee s has the opposite sign, and the finding is explained in terms of Uwaha's scenario.…”
Section: Summary and Discussionmentioning
confidence: 95%
“…!,! ) > 0, growth occurs, while the case of Similarly to previous models 18,39,51,52 , due to the Gibbs-Thomson effect, the cluster solubility ! "…”
Section: Growth and Dissolutionmentioning
confidence: 73%
“…The actual crystal size distributions (CSD) for each enantiomer of the conglomerate crystals are simplified by considering only two arbitrary groups of sizes: large crystals and small chiral clusters 39 . The large crystals in the initially present CSD correspond to the conglomerate seeds, typically of a single chirality, since they are used to control the deracemization outcome.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation